The Role Of Teachers In Instilling Discipline Character Values In Children At Tk It Al-Kiswah, Bengkulu City - Nurul Lailah; Icha Khairiah; Dini Widianti (Yayasan Azhar Amanaa Yogyakarta, 2025)
This study aims to describe the role of teachers in instilling discipline character values in children at TK IT Al-Kiswah, Bengkulu City. A qualitative descriptive approach was employed, with research subjects comprising class teachers, the principal, and Group B students. Data were collected through observation, in-depth interviews, and documentation. Data validity was established through source and technique triangulation, and analysis followed the Miles and Huberman interactive model of data reduction, data display, and conclusion drawing. The results revealed that teachers at TK IT Al-Kiswah have carried out five comprehensive roles in instilling discipline character values: (1) as a role model (uswah hasanah) by demonstrating disciplined behavior in daily learning; (2) as a guide in forming disciplined habits through consistent daily routines; (3) as a motivator providing positive reinforcement for disciplined behavior; (4) as an evaluator continuously monitoring character development; and (5) as a facilitator of a conducive learning environment for discipline formation. Discipline character values were instilled through habituation, exemplary behavior, moral guidance, and integrated supervision within daily learning activities. The findings carry significant implications for the development of character education programs in Islamic early childhood education institutions.